ANALYSIS OF THE JUDGE'S DECISION ON THE JOINDER OF CLAIMS FOR BREACH OF CONTRACT AND UNLAWFUL ACTS (Study of Decision Number: 4268 K/Pdt/2022): ANALISIS PUTUSAN HAKIM TERHADAP PENGGABUNGAN GUGATAN WANPRESTASI DAN PERBUATAN MELAWAN HUKUM (Studi Putusan Nomor: 4268 K/Pdt/2022) - aprillia, fany; Sumriyah (ADHAPER: Jurnal Hukum Acara Perdata, 2025)
This paper analyzes the practice of combining breach of contract and tort lawsuits in Indonesia, with a focus on the Supreme Court Decision No. 4268 K/Pdt/2022. Initially, the case was qualified as a breach of contract by the District Court (Decision No. 48/Pdt.G/2020/PN.Bdg) and the High Court (Decision No. 115/Pdt/2021/PT.Bdg), but later requalified as a tort by the Supreme Court. This study aims to examine the practice of combining breach of contract and tort in Indonesian civil procedure and to analyze the judge’s considerations in changing the legal qualification. This research uses a normative juridical method with statutory and case approaches. Data were collected through literature study of primary legal materials. The analysis used is prescriptive analysis. The results show that in practice, the combination of breach of contract and tort claims is not permissible if they are not closely related, as it may lead to an unclear lawsuit. However, if both are closely connected, systematically separated, and clearly explained, such combination is allowed. In Decision No. 4268 K/Pdt/2022, the claim was considered valid because both legal bases were related to the same object and events, and were presented separately.